WORKSHOP PEMANFAATAN MEDIA PEMBELAJARAN KREATIF DAN INOVATIF MELALUI MEDIA CANVA - Putri Anugrah Cahya Dewi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
The purpose of this workshop activity is to provide new skills for teachers regarding the use of Canva media in designing interesting learning materials. This community service is carried out as a response to the challenges of learning in the digital era. The method used is the workshop method which is divided into several sessions, namely introductory sessions and introduction of material, practical demonstration sessions using Canva, training sessions and project creation, and the last is evaluation and feedback sessions. The evaluation results showed that 95% of teachers were able to understand the use of Canva's features and were able to create learning materials using Canva. In addition, the results of this workshop demonstrated an increase in teachers' understanding and skills in designing creative and innovative learning materials using Canva. With this workshop, it can encourage teachers to collaborate and exchange ideas between teachers in using Canva and provide significant benefits in encouraging teacher innovation as a solution to digital learning challenges.